THE STUDY OF WAYS TO INCREASE INCOME FROM THE DISCARDED LONGAN FRUIT OF BAN PHAEO LONGAN AGRICULTURAL ENTERPRISE GROUP IN BAN PHAEO DISTRICT, SAMUT SAKHON PROVINCE - Thumrongchote, Duangrutai; Kaikaew, Doungtip; Pinjumrus, Weerasit; Preecha, Chatchayasan; Khunlam, Silikanya (Journal of Social Science and Cultural, 2023)
This study has the following objectives: 1) To investigate the requirements for creating products from the discarded longan fruit 2) To develop the discarded longan fruit into healthy processed longan products and 3) To investigate ways of increasing sales of healthy processed longan products using leftover longan fruit by using participatory action research methods. The sample group consisted of 15 members of the Ban Phaeo Longan Large Farming Enterprise Group, drawn from the group president and volunteers. The researcher used focus group discussion method, analysis of the amount of phytochemicals from young fruits and longan flowers, prototype product development and product processing training. The results of the investigation showed that 1) there existed a demand for products produced from dismissed longan fruit in the Ban Phaeo District of Samut Sakhon Province in several distinct forms: 1.1) Processing into goods for healthy food, and 1. 2) Processing into a product used to reduce knee pain; 2) Development The development of nutritionally upgraded longan products from discarded longan has 2 products: dried longan and concentrated longan juice; and 3) Approaches for increasing revenue from healthy processed longan products through using developing the potential of Young SMART Farmers for digital 5.0, combination of local wisdom with innovative agricultural product processing to develop products that is beneficial to health and has a high value or established longan drying factory to provide opportunities for farmers to try to preserve produce in order to avoid the pressure of the middleman's buying price.